2015
DOI: 10.1016/j.pmedr.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise is Medicine™: A pilot study linking primary care with community physical activity support

Abstract: IntroductionExercise is Medicine™ (EIM) is an approach to clinic-based physical activity (PA) promotion. Study aims were to 1) assess the acceptability of current EIM protocols among healthcare providers (providers) and health and fitness professionals (fitness professionals); and 2) pilot test the resultant modified EIM protocols comparing patients referred to community PA programming with patients exposed to the EIM protocols alone.MethodsDuring 2012–2013 in Chattanooga, Tennessee, USA, 30/80 invited provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…28,29 These trials were informed by earlier successes in changing clinician behavior regarding use of the "5 A's" for effective counseling for smoking cessation (eg, ask, advise, agree, assist, and arrange for follow-up). 30 To date, the EIM approach has been adopted in several primary health care clinics 31 as well as broadly across 3 large health care systems in the United States. [32][33][34][35] To date, very few studies have used elements of EIM in the oncology care setting, 16 but there is ample scope and a need to examine integration into cancer care.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 99%
“…28,29 These trials were informed by earlier successes in changing clinician behavior regarding use of the "5 A's" for effective counseling for smoking cessation (eg, ask, advise, agree, assist, and arrange for follow-up). 30 To date, the EIM approach has been adopted in several primary health care clinics 31 as well as broadly across 3 large health care systems in the United States. [32][33][34][35] To date, very few studies have used elements of EIM in the oncology care setting, 16 but there is ample scope and a need to examine integration into cancer care.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 99%
“…Item 13 asked about how PHC professionals were willing to collaborate in PA promotion through a multidisciplinary PHC team. This was scored as important by the experts, in line with the Exercise is Medicine initiative, which encourages multidisciplinarity [ 8 , 9 ]. Finally, item 19, related to the interest on PAP training courses for PHC professionals, was highly scored by all experts, being an indicator to enhance the efficient PAP implementation in PHC settings in accordance with previous studies [ 23 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health benefits of exercise prescriptions are documented and well-known [ 5 ]. Therefore, several approaches are trying to promote PA on prescription (PAP) in healthcare (HC) settings, as for example, the proposal of the WHO for the European Region 2016–2025 [ 6 ], the worldwide strategy of the American College of Sport Medicine that is the Exercise is Medicine ® initiative [ 7 , 8 , 9 ], and others [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to improvements suggested by the professionals, there were calls for a link between the counseling delivered and public, structured physical activity programs, such as physical exercise classes. A pilot study to test the 'Exercise is Medicine' intervention showed that when the counseling for physical exercise was directly linked with referral of patients to a recreation centers, the average effect of increase in moderate-to-vigorousintensity physical activity was larger compared with a group of patients receiving counseling alone after six months of the interventions (Heath et al, 2015). In a national survey involving physicians and nurses working in primary health care in Brazil, Florindo et al (2013) showed that the odds ratio of counseling on physical activity was higher when structured physical activity programs were provided at the primary health care units where the professionals were working.…”
Section: Discussionmentioning
confidence: 99%